P264 Is pleural infection associated with longer survival in mesothelioma? a population-based cohort study using data from hospital episode statistics. (December 2018) - Bibby, AC; De Fonseka, D; Carslake, D; Maskell, NA
Abstract : Background: Historically pleural infection was thought to be associated with longer survival in lung cancer, and small observational studies have reported a similar trend in mesothelioma. The aim of this population-based cohort study was to investigate whether pleural infection was associated with survival with mesothelioma. Methods: Case records for all patients with mesothelioma seen in English hospitals between 01/01/2005 and 1/12/2014 were extracted from Hospital Episode Statistics using International Classification of Diseases Tenth Edition (ICD-10) codes. Episodes of pleural infection were identified. Linked mortality data was obtained from the Office of National Statistics. The primary outcome was all-cause mortality. The explanatory variable was pleural infection. Cox proportional hazards model was used to analyse survival, with pleural infection, chemotherapy and thoracic surgery handled as time-variable co-factors. Findings: Of 22 215 patients with mesothelioma, 512 (2.3%) experienced pleural infection. Overall median survival was 7.0 months. Pleural infection was associated with shorter survival in the immediate post-infection period (up to 30 days – HR 1.78, 95% CI 1.44 to 2.19) and longer term (>30 days – HR 1.77, 95% CI 1.60 to 1.96)). Other factors associated with increased mortality were age, male gender, being diagnosed as an inpatient and having documented asbestos exposure or pleural plaques (see table 1). Receiving chemotherapy and being less economically deprived were associated with longer survival. Discussion: Pleural infection occurs more frequently in patients with mesothelioma than in the general population and is associated with shorter survival. This refutes previous reports suggesting pleural infection may be associated with better outcomes in malignancy. However, certain prognostic data was unavailable, including patients' performance status and tumour histological sub-type, and therefore confounding may have affected this result.